Clinical Study to Evaluate the Accuracy of the Marginal and Internal Fit of Lithium Disilicate Crowns Using Conventional and Digital Techniques - بهرلي ناصر; شموط محمد مروان (Latakia University Journal -Medical Sciences Series, 2020)
The aim of this clinical study was to assess the accuracy of the marginal and internal fit of lithium disilicate crowns made from convenitional impressions and technologies or digital impressions with 3D printing. The study sample included 22 full ceramic crowns (IPS e.max Press lithium disilicate), divided equally into 11 crowns made from a conventional impression with condensation silicone (pvs) and 11 crowns made from a digital impression with an intraoral scanner (i500) for the Korean company (Medit). The patient had good oral health and had the indication of using full ceramic crowns as a result of the presence of old and bad fixed prosthodontics. Abutments prepared according to the principles of preparing the teeth to receive metal-free ceramic prosthodontics, with a deep chamfer finish line on the gingival line. In this study, the marginal and internal gaps were measured by means of a replica technique without cementing crowns. We used a magnifier of the Italian-made OPTICA brand located in the Higher Institute for Environmental Research at Tishreen University with a magnification of 10 x to measure 4 points in the marginal region to study the marginal fit, 4 points on the axial surface and 4 points on the occlusal surface to study the internal fit of each crown. We concluded within the limits of this clinical study: There was no significant statistical difference in the marginal fit between the conventional and digital study groups. The internal gap in the group of digital lithium disilicate crowns was smaller than that of conventional crowns. All the internal and marginal gaps in this study were within clinically acceptable limits.